2014
DOI: 10.1002/anie.201410788
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Directing Omnidirectional Circularly Polarized Reflection from Liquid‐Crystal Droplets

Abstract: Constructing and tuning self-organized three-dimensional (3D) superstructures with tailored functionality is crucial in the nanofabrication of smart molecular devices. Herein we fabricate a self-organized, phototunable 3D photonic superstructure from monodisperse droplets of one-dimensional cholesteric liquid crystal (CLC) containing a photosensitive chiral molecular switch with high helical twisting power. The droplets are obtained by a glass capillary microfluidic technique by dispersing into PVA solution th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
125
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(136 citation statements)
references
References 24 publications
1
125
0
Order By: Relevance
“…Cipparrone and co-workers demonstrated chiral optomechanics involving the interaction of cholesteric droplets and optical tweezers67, and we recently demonstrated and explained how a new type of photonic cross communication develops between monodisperse cholesteric droplets, giving rise to intriguing multi-coloured patterns that are highly tunable8. Several groups have demonstrated interesting variations of the latter theme, including photo-tuning of the colour9 and/or the polarisation10 of the reflected light, as well as encapsulation of cholesteric droplets in hydrogel or rubber shells1112.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Cipparrone and co-workers demonstrated chiral optomechanics involving the interaction of cholesteric droplets and optical tweezers67, and we recently demonstrated and explained how a new type of photonic cross communication develops between monodisperse cholesteric droplets, giving rise to intriguing multi-coloured patterns that are highly tunable8. Several groups have demonstrated interesting variations of the latter theme, including photo-tuning of the colour9 and/or the polarisation10 of the reflected light, as well as encapsulation of cholesteric droplets in hydrogel or rubber shells1112.…”
mentioning
confidence: 68%
“…via photopolymerisation, such that they are kinetically trapped in a non-equilibrium arrangement that could not be reproduced in a step-by-step micromanipulation process. Additional complexity could be achieved by arranging shells in multiple layers9 or by analysing the token in reflection as well as in transmission. The transparency and lack of scattering of the cholesteric shells gives them a characteristic appearance also in transmission, as discussed in detail elsewhere27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[100,201,[205][206][207][208][209][210][211][212] These controllable actions enable CLCs to be used in ground-breaking devices and application. This is because they possess a self-organized helical structure that can be controlled and switched by many stimuli.…”
Section: Cholesteric Lcsmentioning
confidence: 99%
“…14 Moreover, light-directed omnidirectional circularly polarized reflection was achieved in microdroplets of photoresponsive CLCs enabled by chiral diarylethene switch and overcrowded alkene based molecular motors. 15 When confined into spherical microdroplets, CLCs are known to adopt diverse equilibrium configurations which result from the delicate interplay between elasticity, chirality, and surface energy. 16 Recent theoretical studies on cholesteric microdroplets have indicated that frustration imparted by the chirality of CLCs plays a significant role in the structure formations and topological transformations among different configurations.…”
mentioning
confidence: 99%